The Impact of Chain of Servant Leadership on the Effectiveness of Classroom Instruction - Lusi Hapsari Restulingtyas; Ricky Ricky; Zeplin Jiwa Husada Tarigan (Universitas Kristen Petra, 2025)
This study examines the influence of principal servant leadership toward teacher servant leadership, which in turn will influence the classroom instruction at A Christian Faith-Based Senior High School in the Southern part of Surabaya. This quantitative research involved 595 students from 18 classes, ranging from 10th grade to 11th grade, and 12th grade. The data in this research were analyzed using Partial Least Squares on the SmartPLS 3.0 application. The results show that principal servant leadership has a significant effect on teacher servant leadership and classroom instruction. Teacher servant leadership has a significant effect on classroom instruction. Whilst teacher servant leadership was proven to be a partial mediator between principal servant leadership and classroom instruction (VAF=0.4685 or 46,85%). Thus, it is important for schools to pay attention to the development of both principal and teacher servant leadership as they have a significant impact on classroom instruction that eventually will affect students' learning outcomes.